Análise dos perfis de atuação profissional e de competências relativas à inteligência competitiva - Amaral, Roniberto Morato do (2010)
With the aim of contributing to the improvement of efficiency and effectiveness of units of Competitive Intelligence (CI) in the area of people management, the goal of this study was to characterize the profile of Brazilian CI professional approach based on competencies, with a view to establishing the process of People management for competence-based (GPPC). Survey was the research method adopted and applied in the community of professionals involved in CI in Brazil. The results were: a) characterization of the professionals involved with CI b) indicators on the performance of CI in Brazil, c) identification of the attributes of competence of greatest need in carrying out intelligence activities d) identification of the modes of action as dedication to the functions of CI coordinator, analyst, collector, e) display the influence of experience in CI performance on the stages of intelligence, the abilities of the professional and the functions of CI and f) consolidation of a glossary of attributes competence (knowledge, abilities and attitudes) for CI. From the results obtained and the discussion arose around the issue of competence in CI, it was concluded that CI professionals have different profiles of competence according to their performance and professional experience, identified the professional profile and abilities on the CI, its real value to the area of CI will be achieved through the use and application potential in developing a comprehensive model of GPPC applied to teams of CI.